Faith and Assimilation: Italian Immigrants in the US - Stefano Gagliarducci; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
Ethnic religious organizations are often blamed for slowing down immigrants' assimilation in host societies. This paper offers the first systematic evidence on this topic by focusing on Italian Catholic churches in the US between 1890 and 1920, when four million Italians had moved to America, and anti-Catholic sentiments were widespread. Relying on newly collected data on the presence of Italian Catholic churches across counties over time, we implement a difference-in-differences design. We find that Italian churches reduced the social assimilation of Italian immigrants, lowering intermarriage, residential integration, and naturalization rates. We provide evidence that both stronger coordination within the Italian community and negative stereotyping among natives can explain these effects. Yet, Italian churches had ambiguous effects on immigrants' economic outcomes, and increased literacy and ability to speak English among Italian children.
Keywords: J15; N31; Z12; 330; immigration; assimilation; religious organizations